Chikungunya Hospitalization In The Pediatric Population In Brazil: 2017-2021 - Vedana, Gabriela Bedin; Alvarenga, João Victor de Oliveira; Braga, Laura Coimbra Ulhoa Andrade; Scariot, Maiara Flores; Macorin, Rafaela Altoé; Hoffmann-Santos, Hugo Dias; Dombroski, Thais Caroline Dallabona (Seven Editora, 2023)
Chikungunya is a viral disease caused by the pathogen of the same name, of the Alphavirus genus, which can infect humans through the bite of an infected female Aedes aegypti mosquito and Aedes albopictus, the same as dengue. In children, the main clinical manifestations are rash, fever, nausea, vomiting, myalgia and bilateral arthralgia, mainly in the phalanges, wrists and ankles. The diagnosis is performed mainly through the patient’s clinic, requiring a good anamnesis to identify the main risk conditions. OBJECTIVE: To describe the epidemiological profile of pediatric hospitalizations due to Chikungunya in Brazil, highlighting the main signs and symptoms associated with hospitalization. METHODS: An epidemiological, observational, analytical, cross-sectional study was carried out using data from the Disease Information and Notification System (SINAN-DATASUS) of the Ministry of Health regarding confirmed cases of Chikungunya that occurred in all units of the Brazilian federation, in the period from 2017 to 2021, among individuals aged 0 to 11 years. RESULT: A total of 287,898 patients were evaluated according to the geographical distribution of prevalence and factors associated with hospitalization, with fever, severe arthralgia, myalgia and headache being the most common symptoms. Also, the signs and symptoms that most increased hospitalizations were leukopenia, vomiting and petechiae. The rate of hospitalizations for Chikungunya in children aged 0 to 11 years was less than 3% and there were no deaths related to the infection. CONCLUSION: The evolution of Chikungunya in children, despite the association with comorbidities, signs and symptoms, was benign. The health professional must prevent the infection from progressing to hospitalizations, recognizing and intervening in the main signs that lead to this outcome. DOI: https://doi.org/10.56238/colleinternhealthscienv1-101